A Case Study on the Formation of Early Childhood Discipline Character in Single-Parent Families in Cilincing District, North Jakarta - Tamara Yasmine Septiana Tyaskinanthi; Asep Kurnia Jayadinata (Journal of Educational Sciences, 2026)
This study aims to explore the formation of disciplinary character in early childhood within single-parent families in Cilincing district, North Jakarta. The urgency of this research is driven by the increasing number of single-parent households and the importance of character development during early childhood as a critical stage of growth. A qualitative case study method was employed, with data collected through non-participatory observation and semi-structured interviews involving two single-parent families (one mother and one father) with children aged 3 and 5 years. The data were analyzed using the Miles and Huberman model, which includes data reduction, coding, and conclusion drawing and verification. The findings indicate that disciplinary character development in early childhood remains at the stage of external compliance. Both single parents generally apply communicative and democratic parenting strategies, using methods such as logical consequences, rewards, and direct modeling. However, the process is constrained by several factors. Internal constraints include limited time and emotional exhaustion due to the demands of single parenting roles. External constraints are mainly related to inconsistent rule enforcement by substitute caregivers and peer influence. The study highlights the importance of establishing consistent and unified parenting agreements with extended family members to support effective character development.